Ecological corridors for which species? - Merenlender, Adina M.; Keeley, Annika T. H.; Hilty, Jodi A. (THERYA, 2022)
Overwhelming evidence points to the importance of maintaining connectivity given rapidly fragmenting habitats and climate change. Many efforts to identify where ecological corridors should be placed are based on estimates of structural connectivity that take advantage of readily available land-cover data. We provide an overview of structural connectivity methodology and review the various limitations of these methods for functional connectivity -- the degree to which corridors facilitate the movement of organisms. These limitations include not accounting for dispersal complexities and specific habitat requirements of focal species, and invisible barriers to movement. Also, to what extent will the resulting corridors serve the most vulnerable species under a rapidly changing climate? We describe several connectivity-modeling approaches designed to be climate-wise. Assessing species for traits that may make them more susceptible to extinction is one way to prioritize which species warrant additional data collection and demographic analyses to improve the likelihood that corridors will function for them. There is substantial evidence that traits such as limited movement or dispersal ability as well as geographic range and habitat restrictions make species more vulnerable. Therefore, we suggest using these traits to guide focal-species selection. Finally, we discuss the importance of employing new technologies to monitor individual movement and species utilization of corridors varying in width and other characteristics to help plan and verify functional connectivity for these species.